Swimming training prevents coronary endothelial dysfunction in ovariectomized spontaneously hypertensive rats - Claudio,E.R.G. (2017)
Estrogen deficiency and hypertension are considered major risk factors for the development of coronary heart disease. On the other hand, exercise training is considered an effective form to prevent and treat cardiovascular diseases. However, the effects of swimming training (SW) on coronary vascular reactivity in female ovariectomized hypertensive rats are not known. We aimed to evaluate the effects of SW on endothelium-dependent coronary vasodilation in ovariectomized hypertensive rats. Three-month old spontaneously hypertensive rats (SHR, n=50) were divided into four groups: sham (SH), sham plus swimming training (SSW), ovariectomized (OVX), and ovariectomized plus swimming training (OSW). The SW protocol (5 times/week, 60 min/day) was conducted for 8 weeks. The vasodilatory response was measured in isolated hearts in the absence and presence of a nitric oxide synthase inhibitor (L-NAME, 100 µM). Cardiac oxidative stress was evaluated in situ by dihydroethidium fluorescence, while the expression of antioxidant enzymes (SOD-2 and catalase) and their activities were assessed by western blotting and spectrophotometry, respectively. Vasodilation in SHR was significantly reduced by OVX, even in the presence of L-NAME, in conjunction with an increased oxidative stress. These effects were prevented by SW, and were associated with a decrease in oxidative stress. Superoxide dismutase 2 (SOD-2) and catalase expression increased only in the OSW group. However, no significant difference was found in the activity of these enzymes. In conclusion, SW prevented the endothelial dysfunction in the coronary bed of ovariectomized SHR associated with an increase in the expression of antioxidant enzymes, and therefore may prevent coronary heart disease in hypertensive postmenopausal women.